Evidence from 2016 Ethiopian demographic and health survey data: association between post health education maternal knowledge and neonatal danger signs - Kassaw, Mesfin Wudu (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Globally, 4 million infants die in their first 4weeks of life every year; above 8 million infants died before their first year of birthday, and nearly 10 million children died before their 5th birthday. Majority of the deaths were occurred at home because of not receiving health care. In Ethiopia, 120,000 infants died during their first 4 weeks of life. The aim of this study was to assess maternal knowledge about neonatal danger signs and its associations after they had been thought by health professionals in Ethiopia. METHODS: This study used the 2016 Ethiopian Demographic and Health Survey data (EDHS) as a data source. The 2016 EDHS data were collected using a two stage sampling method. All the regions were stratified into urban and rural areas. The study sample taken from the 2016 EDHS data and used in this further analysis was 325. A logistic regression model was used to assess the associations with post health education maternal knowledge on neonatal danger signs. RESULTS: In this study, mothers who had poor knowledge about neonatal danger signs (NDS) were 69.8 % (227) (95 %CI (64.8, 74.8 %). In the final logistic model, wanted no more child ((AOR = 4.15), (95 %CI = 1.12, 15.41)), female child ((AOR = 0.58), (95 %CI = 0.34, 0.98)), primary level maternal education ((AOR = 0.42), (95 %CI = 0.19, 0.92)), secondary level maternal education ((AOR = 0.37), (95 %CI = 0.16, 0.91)), and average size of child ((AOR = 2.64), (95 %CI = 1.26, 5.53)), and small size child ((AOR = 4.53), (95 %CI = 1.52, 13.51)) associated with post health education maternal knowledge about NDS. CONCLUSION: The mothers’ knowledge about NDS is poor even they were gave a birth in health facilities. Wanting of additional child, child sex, maternal education and size of child were associated with NDS knowledge. This indicates that the mode of health education provided for mother might not be appropriate and needs protocol changes.